Purification and Properties of a Diacetyl Reductase from Escherichia coli - Silber, Philip (1974)
A reduced nicotinamide adenine dinucleotide phosphate (NADPH)-dependent reductase with the ability to reduce diacetyl has been isolated from Escherichia coli and has been purified 800-fold to near homogeneity. The product of the reduction of diacetyl was shown to be acetoin. The enzyme proved to catalyze the oxidation of NADPH in the presence of both uncharged α- and β-dicarbonyl compounds. Even monocarbonyl compounds showed slight activity with the enzyme. On the basis of its substrate specificity, it is suggested that the enzyme functions as a diacetyl reductase. In contrast to other diacetyl reductases, the one reported here is specific for NADPH and does not possess acetoin reductase activity. The pH optimum of this enzyme was found to be between 6 and 7. The maximal velocity for the NADPH-dependent reduction of diacetyl was determined to be 9.5 μmol per min per mg of protein and the K(m) values for diacetyl and NADPH were found to be 4.44 mM and 0.02 mM, respectively. The molecular weight was estimated by gel filtration on Sephadex G-100 to be approximately 10,000.